IDENTITY INTEGRATION AND MENTAL HEALTH IN OLDER BLACK GAY MEN. (11th November 2018) - Atakere, D
Abstract: Throughout the course of one's life, individuals reconcile the identity they have developed with the identity assigned to them by various social forces (e.g., parents, friends, etc.). Research suggests that achievement of synthesizing a self-identity and a social identity leads to a sense of psychosocial well-being. We investigated ideas about identity integration and mental health in older Black males (N=169) aged 50 - 81 years (M = 56.4, SD = 6.4) who participated in the Social Justice Sexuality (SJS) survey of LGBT people of color over a 12-month period in the United States. The survey included questions on five broad themes: racial and sexual identity, family formations and dynamics, spirituality and religion, civic engagement, and mental and physical health. Results show that considering sexual identity as an important identity over racial identity has a negative association with mental health (B = -.27, p.02) in older Black gay men. However, considering sexual and racial identity to be equally important identities is positively associated with mental health (B = .36, p<.01) in older Black gay men. Further, data reveal that reports of connection to LGBT community/people have a positive association with mental health (B = .36, p<.01) in older Black gay men. We discuss implications of results for mental well-being in older minority men and human development at levels of individual and society.